Some legal challenges affecting offshore trusts post 2008 financial crisis - Hingun, Mohsin (2014)
The phenomenal growth of offshore trusts valued in trillions of dollars at the end of the last century as a result of its ability to transfer and protect substantial sums of money from the settlor 19s country to overseas jurisdictions with the potential to save, reduce, avoid and evade taxes have been subjected to critical examination by tax authorities, the courts, non-governmental organisations and the media, especially in the years following the 2008 financial crisis. The objective of this paper to briefly introduce the nature and uses of offshore trusts and to focus on some of the important challenges they face in a hostile environment. An area of evolving interest is the secrecy issue inherent in offshore trusts which has been abused as veil for tax avoidance/tax evasion. KEYWORDS: Offshore trusts, 2008 Financial Crisis, Secrecy, Tax Avoidance